Reproduction and opportunity: A study of dual career, aspirations and elite sports in Danish SportsClasses - Skrubbeltrang, L. S.; Karen, D.; Nielsen, J. C.; Olesen, J. S. (International Review for the Sociology of Sport, 2020)
In this article we analyze the patterns of retention in SportsClasses of promising young athletes in Denmark. Since 2005, SportsClasses have provided extra training for potential elite athletes in Grades 7-9 in designated Danish public schools. They were introduced after the Danish Ministry of Culture lowered the age of recruitment for athletes from 15 to 12 in response to increased competition in the world of elite sports. The SportsClasses attempt to balance collaboration between two different organizations: Danish public schools; and sports clubs. Using a survey of the student population in 2013 and a follow-up sample in 2015, we explored the respondents` social backgrounds and experiences in order to understand their likelihood of retention during the program and their career aspirations. Focusing on socioeconomic status (SES), the role of having parents in elite sports, gender, and type of sport, we studied what key experiences and relationships lead students to abandon or sustain their interest in careers related to sports and how this differed for boys and girls. By applying Bourdieu`s concepts of habitus and types of capital, we concluded that the program produced elements of both reproduction and opportunity but that the patterns strongly favored the retention of boys compared to girls. Our findings also suggest that the overlap between school and sport may have lead students from higher SES background to focus on education rather than sports.